S112 TNF-R1 Ubiquitous Scaffolding and Signalling protein (TRUSS) is a regulator of TNF-α induced NF-κ-B activation. (2nd December 2011) - Langton, A J; Horan, I; Farrow, S; Riches, D W; Chilvers, E R; Parfrey, H
Abstract : The pleiotropic cytokine TNFα plays a key role in the pathogenesis of many chronic inflammatory lung diseases, particularly sarcoidosis, asthma and COPD. Due to its broad spectrum of activity however, current anti-TNFα therapies are of limited efficacy in these conditions and are associated with an increased risk of infection and malignancy. Interaction of TNFα with its cognate receptor, TNF-R1 initiates a signalling cascade that leads ultimately to the phosphorylation of the transcription factor NF-kB. This allows NF-kB to shuttle in a co-ordinated manner between the cytoplasm and the nucleus, leading to the up-regulation of genes that are key to cellular inflammatory and apoptotic responses. We propose that the novel TNF-R1 interacting protein TRUSS (TNF-R1 Ubiquitous Scaffolding and Signalling protein), which interacts with members of the TNF-R1 signalling cascade, may regulate this process. A549 cells, which express high levels of endogenous TRUSS, were transfected transiently with siRNA, which resulted in 80±14% (mean±SEM, n=16) knockdown of TRUSS mRNA. TRUSS deficient cells demonstrated a profound early (<1 h) defect in the nuclear translocation of p50/p65 subunits following TNFα stimulation (p<0.05, n=3). As a consequence, in the absence of TRUSS, p50, its precursor phospho-p105, and phospho-p65 were retained in the cytoplasm in these cells following TNFα stimulation. Furthermore, TRUSS depletion caused a reduction in TNFα stimulated NF-kB (p<0.01, n=7) and AP-1 (p<0.01, n=6) luciferase reporter activity; this was associated with a decrease in interleukin 6, RANTES, G-CSF and GM-CSF (p<0.05, n=6) mRNA and protein expression while MCP-1, CXCL5 and IL-8 were not affected. Although TRUSS deplete cells displayed impaired up-regulation of IkBa mRNA in response to TNFα stimulation, the protein response was intact. Upstream signalling molecules TNFR1, TRADD, TRAF2 and RIP were unaffected by TRUSS knockdown. In conclusion, these data suggest a novel role for TRUSS as a scaffold protein involved in the initial nuclear translocation of p50/p65 NF-kB subunits, which regulates the early pro-inflammatory response to TNFα. Hence TRUSS may represent a more selective therapeutic target for modulating TNFα functions.